The Risk Identification On 3" GL BO3-52520 Process Pipelines Using a Risk-Based Inspection Method - Putra, Angga Pratama; Soedarsono, Johny Wahyuadi; Pangesty, Azizah Intan; Yusran asfar, Muhammad Ibkar; Aprizal, Aprizal; Ramadhan, Romal (Teknomekanik, 2022)
The oil and gas industry can contribute significantly to sustainable development by mitigating negative environmental impacts, such as equipment failure. Numerous pipeline failures have occurred due to the dramatic expansion of the oil and gas product distribution pipeline network, which is a significant factor in the offshore gas pipeline network's failure. In general, compared to other equipment types in the industry, planning inspections presents more challenges. Due to a lack of jurisdictional requirements regarding inspection intervals and piping methods. This research aims to ensure the reliability by conducting a risk assessment of the likelihood and consequences of equipment failure, mitigating the impact of that risk, and developing a more optimal inspection plan. This study is focused on API Class 5L Pipe 3" GL BO3-52520. The Routine Inspection Technique (RBI) was implemented in 2016 following the API 581 standard. This semi-quantitative approach is built based on operational data and validated inspection results. According to the risk assessment, the pipeline will have a Medium risk level, with metal losses occurring in each segment. Four years after the risk-based inspection assessment, the recommended inspection plan for gas pipelines is four years.